Antibacterial, cytotoxic and trypanocidal activities of marine-derived fungi isolated from Philippine macroalgae and seagrasses - Notarte, Kin Israel; Yaguchi, Takashi; Suganuma, Keisuke; dela Cruz, Thomas Edison (Acta Botanica Croatica, 2018)
The occurrence and bioactivities of marine-derived fungi were evaluated. A total of 16 morphospecies of marine-derived fungi (MDF) were isolated and identified as belonging to the genera Aspergillus, Fusarium, Paecilomyces, Penicillium, Sclerotinia, Thamnidium and Trichoderma, and five mycelia sterila were isolated from four host macroalgae and two seagrasses. Among these host organisms, the rhodophyte Laurencia intermedia harboured the highest number of isolated MDF. Selected MDF were then assayed and showed to be partially active (10-13 mm ZOI) to active (14-19 mm ZOI) against Pseudomonas aeruginosa and Staphylococcus aureus, and cytotoxic against the brine shrimp Artemia salina nauplii (LD50: 201.56-948.37 µg/mL). The screening led to the selection of five most bioactive morphospecies, all belonging to the genus Aspergillus. These marine aspergilli were subjected to beta-tubulin gene analysis for species identification, and to mass production in different culture media with or without marine salts, and screening of the crude culture extracts for their cytotoxic and trypanocidal activities. Aspergillus tubingensis cultivated in potato dextrose broth with marine salt showed to be the most cytotoxic against P388 (IC50: 1,028 ng/mL) and HeLa (IC50: 1,301 ng/mL) cancer cells. On the other hand, A. fumigatus cultivated in malt extract broth without marine salt showed to be the most potent against Trypanosoma congolense (IC50: 298.18 ng/mL). Our study therefore showed that salinity may influence the bioactivities of some species of MDF.